CLINICAL CHARACTERISTICS OF OVARIAN CLEAR CELL CANCER - M. D. Akhmedova; V. V. Barinov; M. A. Shabanov; K. I. Zhordania; L. I. Bokina; V. I. Peskova; I. V. Panichenko (Опухоли женской репродуктивной системы, 2014)
The research has enrolled 96 patients with rare ovarian clear cell cancer treated at N.N. Blokhin Russian Cancer Research Center from 1978 to 2000. A necessity to divide patients into two groups has emerged after histopathological slide review. The first group included 71 patients with ovarian clear cell carcinoma (OCCC). Twenty five patients with mixed malignant epithelial ovarian tumor (MMEOT) with mandatory presence of clear cell component were included into the second group. Clinical par- ticularities of clear cell ovarian cancer were studied. We performed a comparative study of clinical course of OCCC and MMEOT. Our data suggest that clear cell ovarian cancer has a number of typical clinical and biological particularities both in OCCC and MMEOT.